Seawater intrusion into groundwater, peninsular Malaysia - Ismail, Z.; Aziz, N.A.; Hashim, Roslan (2007)
Industrialization has led to the contamination of the environment including groundwater in the form of chemical and mineral waste Monitoring of important parameters is essential to evaluate the situation and be in a position to intervene if necessary. In this study the parameters monitored were pH, temperature, conductivity and turbidity. Total organics, volatile organic compounds, metals, total hardness, total dissolved solids, anions, phenols, bacteria and radioactivity were also analyzed. This paper focuses mainly on anions with special reference to chlorides, based on data collected from sixty-two monitoring wells throughout the country over a period of three years. The yearly and regional trends were determined, anda course of action is recommended. From the results gathered so far, chlorides have the highest values among the anionic contaminants. This is an indication that perhaps there is seawater intrusion into the groundwater system. However, the levels were not yet critical.